Analisis Sanksi Tindak Pidana Penyimpangan Seksual (Pedofilia) dalam Perspektif Undang-Undang Perlindungan Anak - Nando Joe Syakuur; Rangga Febrio Pratama; Rachmad Naufal Muzhakki; Moch Rofiuddin Mufaqqih; Rena Fandani; Indah Juwita Putri (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The criminal act of pedophilia or sexual violence against children still frequently occurs in Indonesia. Although the penalties for perpetrators and clauses regarding child protection have been regulated by national law, this has not stopped the emergence of pedophiles committing crimes. One of the contributing factors is that pedophiles are often individuals close to the victim's environment. This article is prepared to examine the role of law in Indonesia in providing protection to children who become victims of pedophilia cases. Additionally, this article aims to explore how to impose a deterrent effect on pedophiles based on state policies. The research method used in this article is normative legal research, which focuses on the legislation and legal norms in force. Data collection techniques are conducted through literature studies from various legal sources. Laws regarding penalties for perpetrators of violence against children or pedophilia have been structured in such a way as to address these issues. The government has also formulated regulations concerning legal protection for children, especially for those below the legal age of marriage, as an effort to protect them from pedophilic criminal acts. It is hoped that the government, parents, and the immediate environment of children can implement these policies to create a safe environment free from cases of sexual violence against children.